Genetic exchange with an outcrossing sister species causes severe genome-wide dysregulation in a selfing Caenorhabditis nematode - Xie, Dongying; Ye, Pohao; Ma, Yiming; Li, Yongbin; Liu, Xiao; Sarkies, Peter; Zhao, Zhongying

(untitled) (Genome Research, 2022)
Different modes of reproduction evolve rapidly, with important consequences for genome composition. Selfing species often occupy a similar niche as their outcrossing sister species with which they are able to mate and produce viable hybrid progeny, raising the question of how they maintain genomic identity. Here, we investigate this issue by using the nematode Caenorhabditis briggsae, which reproduces as a hermaphrodite, and its outcrossing sister species Caenorhabditis nigoni. We hypothesize that selfing species might develop some barriers to prevent gene intrusions through gene regulation. We therefore examined gene regulation in the hybrid F2 embryos resulting from reciprocal backcrosses between F1 hybrid progeny and C. nigoni or C. briggsae. F2 hybrid embryos with ∼75% of their genome derived from C. briggsae (termed as bB2) were inviable, whereas those with ∼75% of their genome derived from C. nigoni (termed as nB2) were viable. Misregulation of transposable elements, coding genes, and small regulatory RNAs was more widespread in the bB2 compared with the nB2 hybrids, which is a plausible explanation for the differential phenotypes between the two hybrids. Our results show that regulation of the C. briggsae genome is strongly affected by genetic exchanges with its outcrossing sister species, C. nigoni, whereas regulation of the C. nigoni genome is more robust on genetic exchange with C. briggsae. The results provide new insights into how selfing species might maintain their identity despite genetic exchanges with closely related outcrossing species.